2017
DOI: 10.1093/imrn/rnx151
|View full text |Cite
|
Sign up to set email alerts
|

On Multiple Polylogarithms in Characteristic $p$: $v$-Adic Vanishing Versus $\infty$-Adic Eulerianness

Abstract: Abstract. In this paper, we give a simultaneous vanishing principle for the v-adic Carlitz multiple polylogarithms (abbreviated as CMPLs) at algebraic points, where v is a finite place of the rational function field over a finite field. This principle establishes the fact that the v-adic vanishing of CMPLs at algebraic points is equivalent to its ∞-adic counterpart being Eulerian. This reveals a nontrivial connection between the v-adic and ∞-adic worlds in positive characteristic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Also, Chang-Mishiba and D. S. Thakur concerned v-adic variant ( [10], [19]) and finite variant ( [9], [20]). In this paper, we consider Chang and Mishiba's finite variant ( [9]).…”
Section: Notations and Definitionsmentioning
confidence: 99%
“…Also, Chang-Mishiba and D. S. Thakur concerned v-adic variant ( [10], [19]) and finite variant ( [9], [20]). In this paper, we consider Chang and Mishiba's finite variant ( [9]).…”
Section: Notations and Definitionsmentioning
confidence: 99%
“…Note that Φ ′ is the square matrix of size r cut from the upper left square of Φ. Following [CM19a], for each 1 ≤ i ≤ r we put (2.3.6)…”
Section: 31mentioning
confidence: 99%
“…2.3.2 when replacing Q i by u i can be explicitly written down. We will use this explicit description of G heavily going forward, so we take a moment to recall it from [CM19a]. Let d i be given in (2.3.6) for 1 ≤ i ≤ r, and put…”
Section: Statement Of the Formulaementioning
confidence: 99%
See 1 more Smart Citation
“…[7] formulas, he showed that the multizeta are K-linear combination of their values at tuples with integral co-ordinates. We refer to [12] for some general transcendence results on their values, and to [14], where he and Mishiba study a v-adic analog and show correspondence between the v-adic vanishing and the ∞-adic Eulerian nature, connecting to the torsion phenomena.…”
Section: Dimensions and Transcendence Degreesmentioning
confidence: 99%